2012
DOI: 10.5966/sctm.2012-0022
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Differentiation of Progenitor Cells from Human Adult Adrenal Medulla

Abstract: MEDICINE 2012;1:783-791

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 60 publications
(52 reference statements)
3
42
0
Order By: Relevance
“…Since we have previously shown that human and bovine medullary progenitors express Nestin (Chung et al, 2009;Santana et al, 2012;Vukicevic et al, 2012), we were able to take advantage of the Nestin-GFP mouse model, where enhanced green fluorescent protein is expressed under the regulation of the Nes gene regulatory element (Mignone et al, 2004). In this mouse we detected Nestin-positive cells through expression of GFP, both in the adrenal medulla and cortex ( Fig.…”
Section: Nestin Expressing Progenitorsmentioning
confidence: 90%
See 2 more Smart Citations
“…Since we have previously shown that human and bovine medullary progenitors express Nestin (Chung et al, 2009;Santana et al, 2012;Vukicevic et al, 2012), we were able to take advantage of the Nestin-GFP mouse model, where enhanced green fluorescent protein is expressed under the regulation of the Nes gene regulatory element (Mignone et al, 2004). In this mouse we detected Nestin-positive cells through expression of GFP, both in the adrenal medulla and cortex ( Fig.…”
Section: Nestin Expressing Progenitorsmentioning
confidence: 90%
“…We have for the first time been able to prove the existence of proliferation and differentiation-competent sympathoadrenal progenitor cells within the adult adrenal medulla and have established methods for their isolation from bovine (Chung et al, 2009;Ehrhart-Bornstein et al, 2010;Masjkur et al, 2014) and human (Santana et al, 2012) adrenals. Under low-attachment cell culture conditions, where adherence to the culture dish is prevented, these cells express progenitor markers, have in vitro self-renewing capacity and grow in spheres, which we called chromospheres.…”
Section: Chromaffin Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…*p r0.05; ** r0.01, compared to control; ns =not statistically significant. medulla in an undifferentiated state (Chung et al, 2009;Santana et al, 2012). Chromaffin progenitor cells are characterized by the expression of several progenitor cell markers (Chung et al, 2009;Santana et al, 2012).…”
Section: Ucs Induced Differential and Time-dependent Changes In The Ementioning
confidence: 99%
“…Here we extend our work to the adrenal medulla, a gland whose cells share many properties with neural cells [1,[4][5][6]. Chromaffin progenitor cells share properties with neural stem cells (NSCs) including growth properties and biomarker expression [1,7,8]. There is increasing interest in the involvement of chromaffin progenitor cells in the function of the adrenal medulla, carcinogenesis, and as dopamine sources in Parkinson's disease [9,10].…”
Section: Introductionmentioning
confidence: 99%